Hidden summit ebook - Carr, Robyn (Virgin River, 2011)
Return to Virgin River with the books that started it all... When Connor Danson becomes an unwitting witness to a violent crime, he is forced to leave Sacramento and keep a low profile until the trial is over. He arrives in the tiny mountain town of Virgin River with a chip on his shoulder and an ache in his heart. Leslie Petruso didn't want to leave her hometown, either. But she can't stand another minute of listening to her ex-husband tell everyone that his new wife and impending fatherhood are the best things that ever happened to him. Virgin River may not be home, but it's a place where she can be anonymous. Neither Connor nor Leslie is remotely interested in starting a new relationship...until they meet one another. Even they can't deny they have a lot in common—broken hearts notwithstanding. And in Virgin River, no one can stay hidden away from life and love for very long... Look for What We Find by Robyn Carr, a powerful story of healing, new beginnings and one woman's journey to finding the happiness she's long been missing. Order your copy today!